India on the Move Volume-3 - Planning Commission (Planning Commission, 1999)
Even though planning has been a central tenet of our approach to economic development since Independence, it has neither become ideologically rigid nor methodologically stultified. Each of our Plans has reflected the changing imperatives of the times and the theoretical and experiential developments from around the world. Some of the changes have been strikingly bold, while others somewhat modest.
Government of India Planning Commission
Government of India Planning Commission